اللهجة والمجتمع -انعكاس النظم الاجتماعية والثقافية في لهجة وادي سوف - عماري, مباركة (University of Eloued جامعة الوادي, 2021)
إن اللّهجة بكونّها ظاهرة اجتماعية بالدرجة الأولى، فهي المرآة العاكسة لهذا الواقع الاجتماعي المعيش، ولا يمكن الكشف عن ظواهرها اللغوية بالدّراسات اللّسانية الحديثة، إلا بربطها بالجانب الاجتماعي والثّقافي، وذلك من خلال منهج علم اللّغة الاجتماعي أو علم السّوسيولسانيات، لذا تهدف هذه الدّراسة إلى الكشف عن علاقة اللّهجة بالنّظم الاجتماعيّة والثقافيّة وبيان آثارها التي تركتها تلك النّظم على مستوياتها اللّهجية. كالمستوى الفونولوجي أو الصوتي الذي تأثر بالنّظم الاجتماعيّة والثّقافيّة من خلال عدّة ظواهر مختلفة، كالاستمرارية والتّوارث بين الأجيال والنّمط المعيشي والفلاحي والنّمط الريفي والمدني، كل هذه الأمور وغيرها أثرت على نطقهم لبعض الأصوات، ممّا جعلتهم يميلون في نطقهم أحيانًا للتفخيم والجهر والإمالة والإبدال والنّبر والتّنغيم(...)إلخ. كما أن المستوى المورفوتركيبي تأثر بالظّواهر الطبقية، كالفئة المتعلمة وغير المتعلمة وفئة القبائل البدوية والحضارية والنّمط الصحراوي في ابتعاد أماكنه واتساعها، فهذه الظّواهر وغيرها جعلت البعض منهم يؤثرون في تغيير نطق بنية المفردات وتراكيبها أحيانًا، فقد يميلون بعضهم لتراكيب الطويلة والبعض الآخر لتراكيب القصيرة المختصرة. أمّا عن المستوى الدّلالي فأثر فيه ذلك التّفاعل والاحتكاك والاستمرارية والزّمن والتّطور والدّيناميكية الموجودة بين الفرد ومحيطه من ظواهر اجتماعية وثقافية وعادات وتقاليد ومعتقدات ومستويات ثقافية بين الأفراد وغيرها، ممّا جعل بعض مفردات لهجتهم تتطور وتتغير دلالاتها أثناء النّطق، وذلك بتعميمها أو تخصيصها أو تغير مجالها. وفي الأخير حاولنا أن نختمها بخاتمة تلخص كل النتائج المتوصل إليها مع محاولة اظهار علاقة التأثير والتأثر الرابطة بين اللّهجة المنطوقة وبين مجتمع وادي سوف. The dialect is primarily a social phenomenon, as it is the reflective mirror of this lived social reality, and its linguistic phenomena cannot be revealed with modern linguistic studies, except by linking them to the social and cultural aspect, through the methodology of social linguistics or sociology, so this study aims to reveal The relationship of dialect to social and cultural systems, and its effects on the dialectical levels Like the phonological or phonological level that was affected by social and cultural systems through several different phenomena, such as continuity and intergenerational inheritance, the living and agricultural style, and the rural and civil style, all these and other things affected their pronunciation of some voices, which made them inclined in their pronouncement sometimes to exaggeration, openness, tilt, substitution, tone, and toning (...)etc. The morphotypic level was also affected by class phenomena such as the educated and uneducated category and the Bedouin and civilized tribes and the desert pattern in its distance and breadth, these phenomena and others have made some of them influence changing the pronunciation of the vocabulary structure and its structures sometimes, some of them may tend to long structures and others to short short structures. As for the semantic level, the interaction, friction, continuity, time, development, and dynamism that exist between the individual and his surroundings include social and cultural phenomena, customs, traditions, beliefs and cultural levels between individuals and others, which made some vocabulary of their dialect evolve and its meanings change during pronunciation, by generalizing, allocating or changing its field. Finally, we tried to conclude it with a conclusion that summarizes all the results reached with an attempt to show the relationship of influence and influence between the spoken dialect and the Wadi Souf community.
أطروحة دكتوراه في الأدب العربي تخصص اللسانيات العامة
Keywords: اللهجة، المجتمع، اللسانيات الاجتماعية، لهجة وادي سوف; Dialecte, société, sociolinguistique, dialecte de Wadi Suf